Seismic and sequence stratigraphy of the Palaeocene carbonates at the western margin of Cyrenaica platform, NE-Libya - El-Shari, Saad M. (Libyan Journal of Science &Technology, 2022)
The work of this research focuses on seismic sequence stratigraphy of the Palaeocene succession in the western margin of Cyrenaica Platform. The availability of a good seismic and well data provided the opportunity for testing seismic and sequence stratigraphy techniques in the area. This area, geologically, lies on a hinge-line between the subsiding Sirte Basin to the west and the stable Cyrenaica Platform to the east. The immediate objective of this research is to better understand the stratigraphic and facies variation within the Palaeocene sequence in this area. By the end of the Palaeocene the major tectonic rifting event which formed the Sirte Basin had almost ceased. The subsequent history of the basin was represented the post-rift depositional phase of basin development. The carbonate platform on the western margin of the Cyrenaica Platform contains a record of composite relations between the factors that controlled carbonate platform deposition during the Tertiary. Evolution of this carbonate margin is an excellent example since it clearly shows how the history of this type of margin is dominated by interaction between regional effects, and governed by thermal subsidence consequent upon extension. The shelf edge is the most sediment-starved part of the margin, and given suitable climatic conditions, carbonate deposition can occur at rates equal to subsidence thus maintaining and building the platform. The most important facies and stratigraphic relations of Palaeocene sequence are analysed and discussed in terms of platform development and the principal factors that influenced patterns of sedimentation and the production of carbonate. Furthermore, the sequence stratigraphic and seismic facies study of this interval explain the Paleocene geological history of the Sirte Basin, an essential step in any Hydrocarbon exploration program